(untitled) (Geologica Macedonica, 2021)
Diatomite is one of the most intensively examined raw materials in the materials industry with a broad range of various applications. The diatomite sample, collected from Vitačevo plateau in the vicinity of Kavadarci, was fully characterized by means of physical-mechanical, chemical, XRPD, SEM, TEM, DTA/TGA and IR techniques. The physical-mechanical features pointed out to soft, light, white to gray rock with shell-like structure exhibiting compressive strength from 4.65–4.88 MPa in dry form, whereas the total porosity ranges 70–72% and the density is 2.06–2.09 g/cm3. The chemical analysis of the diatomite revealed that SiO2 content exceeds 91%. The results from the X-ray powder diffraction indicate predominant amorphous SiO2 phase associated with minor presence of crystalline quartz, muscovite, chlorites and plagioclase. The IR spectrum of the diatomite manifested characteristic bands for amorphous silica at 799 cm–1 and 1101 cm–1. DTA/TGA results display great thermal stability of the sample remaining amorphous up to 1050ºC whereas the SEM analysis determined the morphology, surface characteristics and the nanometric pores in the raw material. Thus, the studied diatomite is classified as a natural nanomaterial that is suitable for broad application in various construction materials, refractory ceramics, special oxide ceramics, and also finds potential use in filtering, adsorbent, catalysts, food and pharmaceutical industries.